Roundabouts as safe and modern solutions in transport networks and systems 15th Scientific and Technical Conference "Transport Systems, Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, selected papers /: 15th Scientific and Technical Conference "Transport Systems, Theory and Practice 2018", Katowice, Poland, September 17-19, 2018, selected papers. (2019) - Unknown
No abstract available